Molecular footprint and pathways of DOM biotransformation in the Yangtze River - Guangrui Yang; Farong Chen; Songchol Kang; Jiaming Chen; Chu Zhao; Lize Meng; Xinyi Zhang; Jiayue Lu; Shuaidong Li; Zihao Bian; Jian Zhou; Qihao Jiang; et al. (Water Research, 2026)

Impacts of carbon source type on metabolic pathways and microbial synergy in the simultaneous anammox and endogenous denitrification process - Wenlong Liu; Yuyan Zhang; Chenhao Yue; Jiaming Wang; Jun Li; Huijie Lu; Shilong He; Yongzhen Peng (Bioresource Technology, 2026)

Sustainable urban transitions in resource-based cities: How transition willingness translates into external green technology acquisition - Jiachuan Liu; Peiyuan Zhang; Jiaming Li; Shuo Lu; Wenzhong Zhang (Sustainable Production and Consumption, 2026)

LvBlimp1 and LvHes1 coregulate the function of macrophage-like phagocytes in shrimp hemolymph - Jiaming Liu; Yaohui Chen; Wenyong Jiang; Zhiyao Lu; Nuo Lin; Qingyun Liu; Xiuli Chen; Yongzhen Zhao; Fan Wang (Fish & Shellfish Immunology, 2026)

Thermal-buffering cellulose aerogels with competitive hydrogen bonding: Dual-enthalpy synergy for efficient solar desalination - Mengqi Lu; Shuyue Zhang; Jiangquan Yang; Wei Li; Shuangfei Wang; Shouxin Liu; Jiaming Sun; Shuangxi Nie (Chemical Engineering Journal, 2026)

Derivation and evaluation of Landsat-derived annual aboveground biomass maps for Arctic and Boreal North America, 1984-2022 - Wanwan Liang; Olivier van Lier; Mark A. Friedl; James T. Randerson; Brendan M. Rogers; Arden Burrell; Kai-Ting Hu; Piotr Tompalski; Matthew J. Macander; Daryl Yang; Douglas C. Morton; Eric Bullock; et al. (Remote Sensing of Environment, 2026)

3D laser scanning-based geometry reconstruction and stress evaluation of a KK-type cast steel node for offshore wind turbine jacket structures - Feng Shi; Hui Jin; Lu Xu; Jiaming Liu; Jiahao Hu; Haihan Jiao (Ocean Engineering, 2026)

Humic acid-mediated activation of antimony colloid during soil redox cycles: Mechanisms and environmental implications - Xiongkai Zheng; Jiaming Xu; Haiming Cai; Qiming Mo; Yihao Li; Qixian Fu; Lijuan Zeng; Yongyang Wang; Xueqin Tao; Zhi Dang; Guining Lu (Journal of Hazardous Materials, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

Olfactory Valence-Processing Deficits and Aberrant Brain Network Connectivity Underlie Social Dysfunction in Shank3-/- ASD Model Mice - Dingding Yang; Qian Liu; Hangjun Ran; Teng Xue; Yifan Lu; Xiao Yang; Jiaming Wang; Ling Liu; Wenting Wang; Binbin Nie; Guohong Cai; Shengxi Wu (Neuroscience Bulletin, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

Transcriptomics analyses reveal microgravity triggers estrogen synthesis amidst degeneration and aging in human ovarian granulosa cells - Changjian Yin; Jiaming Zhang; Zihang Cheng; Fang He; Haiquan Lu; Shigang Zhao (Life Sciences in Space Research, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Proof-of-concept evaluation of a 3D laser profiling system prototype for real-time woody breast detection of broiler breast fillets - Jiaming Zhang; Yuzhen Lu (Journal of Food Engineering, 2026)

Side-deep placement of controlled-release urea combined with alternate wetting and drying irrigation achieves sustainable intensification of rice production in the rice–wheat system - Yuan Wang; Li Zhang; Kai Ming; Lin Cao; Song Guo; Jiaming Lu; Ziwei Li; Weiling Wang; Can Zhao; Fengping Yang; Ke Xu; Hongcheng Zhang; et al. (Field Crops Research, 2026)

Different geographical patterns and assembly mechanisms of phytoplankton and benthic diatoms: a case study in a cold temperate wetland cluster - Yongxu Duan; Zhengxun Li; Jiaming Liu; Zheng Hou; Henglin Xiao; Yan Liu; Yawen Fan; Xinxin Lu (Hydrobiologia, 2026)

Prediction of Heterogeneous Shale Lithology in the Kaijiang–Liangping Trough Based on Dream Optimization Algorithm and Support Vector Machine - Lexin Yuan; Zhiming Xu; Haofei Sun; Jungang Lu; Luchuan Zhang; Xiangdong Yin; Jiaming Li (Mathematical Geosciences, 2026)

Modern pollen analysis on peatlands across monsoonal China and its implications for reconstruction - Shu Chen; Mengmeng Wang; Chunmei Ma; Tianyi Tang; Rui Ke; Jiaming Hou; Xinrong Zhang; Zhuo Zheng; Xiayun Xiao; Yan Zhao; Huayu Lu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Post-mortem analysis of degradation behavior in catalyst layers of proton exchange membrane fuel cell under near-water boiling temperature - Daijun Yang; Bo Zhou; Yirui Lu; Jiaming Lou; Bing Li; Pingwen Ming (Fuel, 2026)

Post-mortem analysis of the degradation behavior of the fuel cell gas diffusion layer under near to water boiling point conditions - Yirui Lu; Daijun Yang; Jiaming Lou; Bo Zhou; Xiangyang Zhou; Xiangmin Pan; Bing Li; Pingwen Ming (Chemical Engineering Journal, 2026)

A bead-based dendritic amplification system for multiplex miRNA detection - Feiyang Qian; Rui Zhu; Yao Lu; Tenghua Zhang; Yuqing Zhu; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2026)

Analysis of large deformation characteristics of deep foundation pit at a subway station constructed by the tunnel-before-station method - Jiaming Liang; Wenji Su; Tingjin Liu; Huifeng Wu; Lele Lu; Huashan Zhong; Shuyang Zhou (European Journal of Environmental and Civil Engineering, 2025)

Nonlinear relationship between built environment and commute mode choice: A comparison of commuters within and beyond the long commute threshold - Ming Yu; Zhaomin Tong; Jiaming Yang; Yanchi Lu; Yang Liu; Yanfang Liu; Yaolin Liu (Journal of Transport Geography, 2025)

Spatiotemporal changes in global cropland fire activity from 2003 to 2020 - Jiaming Wang; Xiaoting Zhong; Jie Zhao; Xiaofan Shen; Mengyu Wang; Junhao He; Xiaohan Meng; Qiuling Chen; Xinrui Lu; Liang Wang; Chao Yue (Global and Planetary Change, 2025)

On-demand cinnamaldehyde releasing from gelatin-based active hydrogel activated by lactic acid for pork meat preservation: A novel “one-step-ahead” strategy - Peng Shan; Jiaming Wu; Jian Du; Chenglong Fu; Jinwen Hu; Yehan Tao; Jie Lu; Yanna Lv; Xiaodong Xia; Jijuan Cao; Haisong Wang (Food Chemistry, 2025)

Convenient DNA extraction integrated with dual RPA-LFA technology for simultaneous detection of Salmonella and Listeria monocytogenes - Jiaming Huang; Jing Sun; Xinyi Pang; Xiangfei Li; Xiaomei Bie; Yingjian Lu (Food Bioscience, 2025)

CRISPR/Cas12b-mediated one-tube live cell assay facilitates Salmonella typhimurium detection in poultry meat - Yongjin Dai; Jiaming Huang; Moran Zhang; Xinyi Pang; Xiangfei Li; Jing Sun; Yingjian Lu (Food Bioscience, 2025)

Thermostatic nucleic acid amplification technology in foodborne pathogen detection: opportunities and challenges - Moran Zhang; Jiaming Huang; Yongjin Dai; Shanshan Jin; Qianqian Jia; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (Critical Reviews in Food Science and Nutrition, 2025)

Unveiling spatiotemporal patterns of urban ecosystem services flows in urban thermal environments: Insights from residency, age, and gender disparities - Jiaming Yang; Zhaomin Tong; Yaolin Liu; Yanfang Liu; Jiwei Xu; Yanchi Lu; Yifan Xie; Yang liu (Sustainable Cities and Society, 2025)

Corrigendum to “Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms” [Catena 254 (2025) 108882] - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Selective expansion of TCF7-expressing tumor-reactive T cell subpopulations during ovarian tumor-infiltrating T cell production ex vivo - Dingfeng Liu; Ting Zhang; Qinli Sun; Dongli Cai; Yanan Lou; Genyu Wang; Bowen Xie; Yicheng Zhu; Chong Wang; Zhouping Lu; Chenfei Liu; Yuan Li; et al. (Science China Life Sciences, 2025)

Differential impacts of rain event and continuous rainfall on biological phosphorus removal of a full-scale wastewater treatment plant: performance analysis and optimization strategies - Jiaming Hu; Lu-Man Jiang; Lihua Wang; Xinya Ding; Xinhong Han; Yan Zhang; Haijuan Wei; Zhan Qiu; Ying An; Zhen Zhou (Journal of Environmental Management, 2025)

Better inversion of rice nitrogen nutrition index at early panicle initiation stage using spectral features, texture features, and wavelet features based on UAV multispectral imagery - Ziwei Li; Yuliang Zhang; Jiaming Lu; Yuan Wang; Can Zhao; Weiling Wang; Jianjun Wang; Hongcheng Zhang; Zhongyang Huo (European Journal of Agronomy, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Study on hot spot stress distribution and fatigue life assessment of KK-type cast steel nodes based on scaled model test - Haihan Jiao; Jiaming Liu; Lu Xu; Feng Shi; Hui Jin; Yongchun Fan (Ocean Engineering, 2025)

Carbon storage in typical ecosystems of coastal wetlands in Jiangsu, China: Spatiotemporal patterns and mechanisms - Rui Zhong; Lijie Pu; Jiayi Xie; Jiaming Yao; Lu Qie; Gaili He; Xiaoqing Wang; Rui Zhang; Jiahao Zhai; Zhongshun Gong; Yumeng Lu; Jiawei Tao; et al. (CATENA, 2025)

Evaluation of Geosites in Changbaishan Global Geopark based on Fuzzy AHP and TOPSIS - Jiaming Li; Jinxin He; Peng Lu; Xiangjin Ran; Jian Yi (Geoheritage, 2025)

Tree age estimation across the U.S. using forest inventory and analysis database - Jiaming Lu; Chengquan Huang; Karen Schleeweis; Zhenhua Zou; Weishu Gong (Forest Ecology and Management, 2025)

Development of dual polymerase spiral reaction for detection of Listeria monocytogenes and Staphylococcus aureus simultaneously - Moran Zhang; Hongzhou Chen; Jiaming Huang; Yongjin Dai; Yujuan Liu; Xiyao Zhou; Xiangfei Li; Xinyi Pang; Jing Sun; Yingjian Lu (International Journal of Food Microbiology, 2025)

Efficient Removal of Cr(VI) by Bamboo-Derived Biochar Supported Nano Zero-Valent Iron: Insights into Performance and Mechanism - Yiqun Xu; Jiaming Guo; Siqi Wen; Xiaoyu Shi; Yunlong Zhu; Jianbing Lu; Yang Gao; Mingjuan Zhang; Wenjing Xue (Water, Air, & Soil Pollution, 2025)

Excessive nitrogen application reduces eating quality by changing the starch molecular structure and physicochemical properties of inferior grains - Can Zhao; Yue Chen; Kunlun Liu; Guangming Liu; Jiaming Lu; Weiling Wang; Zhongyang Huo (Journal of Cereal Science, 2025)

Rapid and accurate AuNPs-sodium deoxycholate-propidium monoazide-qPCR technique for simultaneous detection of viable Listeria monocytogenes and Salmonella - Jiaming Huang; Xinyi Pang; Xiangfei Li; Xiaomei Bie; Jing Sun; Yingjian Lu (Food Control, 2024)

Quasi-homogeneous photoelectrochemical organic transformations for tunable products and 100% conversion ratio - Cheng Lin; Yuan Lu; Jiaming Miao; Zhongyuan Ma; Youngmoon Choi; Yan Yang; Chaoran Dong; Jinyou Shen; Jong Hyeok Park; Kan Zhang (Science Bulletin, 2024)

Water-induced surface ordering facilitating the microcutting of ductile metals - Jiong Zhang; Xiaopeng Wang; Lu Ma; Shibo Xi; Jiaming Zhan; Ruipeng Li; Yonghua Du; Junmin Xue; Hao Wang (Journal of Cleaner Production, 2024)

Co-governance of open pit mines across China based on exposure risk assessment of particulate matter - Shuo Lu; Wenzhong Zhang; Peng Zeng; Jiaming Li (Journal of Cleaner Production, 2024)

Hotspots of wetland loss to impervious surfaces in the conterminous United States - Zhenhua Zou; Chengquan Huang; Megan W. Lang; Ling Du; Greg McCarty; Jeffrey C. Ingebritsen; Jane Harner; Rusty Griffin; Weishu Gong; Jiaming Lu (Science of The Total Environment, 2024)

A novel intelligent indoor fire and combustibles detection method based on multi-channel transfer learning strategy with acoustic signals - Zhihua Wang; Zipeng Zhang; Zhuoyue Wang; Jiaming Lu; Weiguang An (Process Safety and Environmental Protection, 2024)

Hydrocarbon Source and Relationship between Hydrocarbon Charging Process and Reservoir Tight Period of the Denglouku Formation Tight Sandstone Gas Reservoirs in the Xujiaweizi Fault Depression, Songliao Basin - Huan Miao; Zhenxue Jiang; Jiaming Lu; Chengju Zhang; Lidong Shi; Lidong Sun; Liang Yang; Peng Shang (Natural Resources Research, 2024)

Towards sustainable development in resource-based cities: Assessing the effects of extraregional technology and investment on the low-carbon transition - Shuo Lu; Jiaming Li; Wenzhong Zhang; Fan Xiao (Journal of Environmental Management, 2024)

Alterations in Dynamic Functional Connectivity in Patients with Cerebral Small Vessel Disease - Futao Chen; Qian Chen; Yajing Zhu; Cong Long; Jiaming Lu; Yaoxian Jiang; Xin Zhang; Bing Zhang (Translational Stroke Research, 2024)
Cerebral small vessel disease (CSVD) is a common disease that seriously endangers people’s health, and is easily overlooked by both patients and clinicians due to its near-silent onset. Dynamic functional connectivity (DFC) is a new concept focusing on the dynamic features and patterns of brain networks that represents a powerful tool for gaining novel insight into neurological diseases. To assess alterations in DFC in CSVD patients, and the correlation of DFC with cognitive function. We enrolled 35 CSVD patients and 31 normal control subjects (NC). Resting-state functional MRI (rs-fMRI) with a sliding-window approach and k -means clustering based on independent component analysis (ICA) was used to evaluate DFC. The temporal properties of fractional windows and the mean dwell time in each state, as well as the number of transitions between each pair of DFC states, were calculated. Additionally, we assessed the functional connectivity (FC) strength of the dynamic states and the associations of altered neuroimaging measures with cognitive performance. A dynamic analysis of all included subjects suggested four distinct functional connectivity states. Compared with the NC group, the CSVD group had more fractional windows and longer mean dwell times in state 4 characterized by sparse FC both inter-network and intra-networks. Additionally, the CSVD group had a reduced number of windows and shorter mean dwell times compared to the NC group in state 3 characterized by highly positive FC between the somatomotor and visual networks, and negative FC in the basal ganglia and somatomotor and visual networks. The number of transitions between state 2 and state 3 and between state 3 and state 4 was significantly reduced in the CSVD group compared to the NC group. Moreover, there was a significant difference in the FC strength between the two groups, and the altered temporal properties of DFC were significantly related to cognitive performance. Our study indicated that CSVD is characterized by altered temporal properties in DFC that may be sensitive neuroimaging biomarkers for early disease identification. Further study of DFC alterations could help us to better understand the progressive dysfunction of networks in CSVD patients.

Cooling and optimizing urban heat island based on a thermal knowledge-informed multi-type ant colony model - Zhaomin Tong; Jiaming Yang; Yaolin Liu; Ziyi Zhang; Sui Liu; Yanchi Lu; Bowen Pang; Rui An (Remote Sensing of Environment, 2024)

An intelligent control method for PEMFC air supply subsystem to optimize dynamic response performance - Qingqing Su; Jiaming Zhou; Fengyan Yi; Donghai Hu; Dagang Lu; Guangping Wu; Caizhi Zhang; Bo Deng; Deming Cao (Fuel, 2024)

Design optimisation of structures made of a small number of prescribed building blocks - Hongjia Lu; Ting-Uei Lee; Jiaming Ma; Yi Min Xie (Engineering Structures, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Cas-Rainbow: Cas12a-driven single-reaction multiplex detection system - Yuqing Zhu; Jianming Zhou; Yuxin Liang; Yao Lu; Shujun Zhou; Feiyang Qian; Tenghua Zhang; Yan Sheng; Jiaming Hu (Chemical Engineering Journal, 2024)

Full-scale experimental study on evacuation behavior characteristics of underwater road tunnel with evacuation stairs under blocked conditions - Kunkun Chu; Baochao Xie; Zhisheng Xu; Dan Zhou; Lu He; Jiaming Zhao; Houlin Ying (Tunnelling and Underground Space Technology, 2023)

Association between mercury exposure and lung function in young adults: A prospective cohort study in Shandong, China - Jiaming Miao; Shurong Feng; Siqi Dou; Yang Ma; Liu Yang; Lailai Yan; Pei Yu; Yao Wu; Tingting Ye; Bo Wen; Peng Lu; Shanshan Li; et al. (Science of The Total Environment, 2023)

Magnetic nanometer combined with microwave: Novel rapid thawing promotes phenolics release in frozen-storage lychee - Canhua Xu; Jiaming Lu; Qingzhu Zeng; Junjia Zhang; Lihong Dong; Fei Huang; Yingbin Shen; Dongxiao Su (Food Chemistry, 2023)

Experimental investigation on pressure oscillation induced by steam injection into subcooled water through an opposite nozzle - Haitao Ren; Dingding Liang; Tao Lu; Jie Wang; Pei Yu; Jie Li; Jiaming Zhao; Ping Xiong (Annals of Nuclear Energy, 2023)

Inspired by philosophizing of “point to area”: Ion pre-intercalation induces the reconstitution of interlayer environment of MXene for lithium storage - Miao Liu; Xin Qu; Yixuan Wang; Yukai Zhang; Cuimei Zhao; Bo Liu; Xiangxin Xue; Junkai Zhang; Zhao Wang; Jiaming Li; Wenjuan Han; Shichong Xu; et al. (Chemical Engineering Journal, 2023)

Brain microstructural alterations in the left precuneus mediate the association between KIBRA polymorphism and working memory in healthy adults: a diffusion kurtosis imaging study - Junxia Wang; Sichu Wu; Yi Sun; Jiaming Lu; Jilei Zhang; Yu Fang; Zhao Qing; Xue Liang; Wen Zhang; Qian Chen; Xin Zhang; Bing Zhang (Brain Imaging and Behavior, 2022)
Kidney and brain expressed protein (KIBRA) rs17070145 is associated with working memory function and cognitive processes. However, the neural mechanisms underlying these associations are not fully understood. This study aimed to explore the effect of KIBRA polymorphism on brain microstructure and blood oxygenation level dependent (BOLD) fluctuations using diffusion kurtosis imaging (DKI) and resting-state functional magnetic resonance imaging (fMRI) in 163 young adults. We also investigated that whether the imaging alterations mediated the association between KIBRA gene and working memory performance. Voxel-based analysis of DKI data showed that KIBRA C-allele carriers exhibited increased axial diffusivity (AD), radial diffusivity (RD) and mean diffusivity (MD) as well as decreased fractional anisotropy (FA), mean kurtosis (MK) and radial kurtosis (RK) compared with KIBRA TT homozygotes, primarily involving the prefrontal lobe, left precuneus and the left superior parietal white matter. Meanwhile, KIBRA C-allele carriers exhibited decreased amplitude of low-frequency fluctuation (ALFF) in the left precuneus compared to KIBRA TT homozygotes. Mediation analysis revealed that the DKI metrics (MK and RK) of the left precuneus mediated the effect of the KIBRA polymorphism on working memory performance. Moreover, the MK and RK in the left precuneus were positively correlated with ALFF in the same brain region. These findings suggest that abnormal DKI parameters may provide a gene-brain-behavior pathway in which KIBRA rs17070145 affects working memory by modulating brain microstructure in the left precuneus. This illustrates that DKI may provide additional biological information and reveal new insights into the neural mechanisms of the KIBRA polymorphism.

Simulations of sea fog case impacted by air–sea interaction over South China Sea - Liguo Han; Shuqin Zhang; Feng Xu; Jingjing Lü; Zebin Lu; Guiling Ye; Siqi Chen; Jianjun Xu; Jiaming Du (Frontiers in Marine Science, 2022)
A sea fog event in the South China Sea was simulated using a coupled ocean–atmosphere model (WRF for the atmosphere and ROMS for the ocean). Offshore and onshore visibility, liquid water content, air temperature, humidity, and wind speed observations and MICAPS data were utilized to validate the model results. The results of the coupled model were also compared with those of the uncoupled atmosphere model. Sea fog duration in the coupled model was closer to offshore and onshore observations, but the uncoupled model emptily forecasted offshore fog, and underreported onshore fog. Air–sea temperature difference played an important role in regulating the formation and dissipation of sea fog. The decrease of sea surface temperature in the coupled model cooled the low-level atmosphere, promoted the condensation of low-level water vapor, and increased the low-level water vapor. The decrease of air–sea temperature difference strengthened the low-level stable stratification, which weakened the horizontal wind speed and favored the formation and development of sea fog. Rising wind speed was the major driver of fog dissipation.

Consistency correction of echo intensity data for multiple radar systems and its application in quantitative estimation of typhoon precipitation - Shuai Zhang; Jing Han; Bingke Zhao; Zhigang Chu; Jie Tang; Limin Lin; Xiaoqin Lu; Jiaming Yan (Frontiers of Earth Science, 2022)

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Effects of High-Dose of Copper Amino Acid Complex on Laying Performance, Hematological and Biochemical Parameters, Organ Index, and Histopathology in Laying Hens - Qin Zhou; Jiaming Zhu; Bing Liu; Jialing Qiu; Xintao Lu; Brian Curtin; Fei Ji; Dongyou Yu (Biological Trace Element Research, 2021)

Influences of ABC transporter and CYP3A4/5 genetic polymorphisms on the pharmacokinetics of lenvatinib in Chinese healthy subjects - Jiaming Li; Xiaoqian Wang; Chen Ning; Zhaoyu Wang; Yao Wang; Ming Zheng; Siliang Zhang; Yang Lu; Yongjie Zhang; Ning Li; Xijing Chen; Di Zhao (European Journal of Clinical Pharmacology, 2020)

Biological and chemical compositions of atmospheric particulate matter during hazardous haze days in Beijing - Zhendong Guo; Zhongyi Wang; Lu’an Qian; Zongzheng Zhao; Chunmao Zhang; Yingying Fu; Jiaming Li; Cheng Zhang; Bing Lu; Jun Qian (Environmental Science and Pollution Research, 2018)

Genetic mapping and molecular marker development for Pi65(t), a novel broad-spectrum resistance gene to rice blast using next-generation sequencing - Wenjing Zheng; Yan Wang; Lili Wang; Zuobin Ma; Jiaming Zhao; Ping Wang; Lixia Zhang; Zhiheng Liu; Xiaochun Lu (Theoretical and Applied Genetics, 2016)

Genotype Analysis of Collagenase Gene by PCR-SSCP in Vibrio alginolyticus and its Association with Virulence to Marine Fish - Lu Yishan; Feng Jiaming; Wu Zaohe; Jian Jichang (Current Microbiology, 2011)

Evaporite karst and resultant geohazards in China - Lu Yaoru; Zhang Feng’e; Qi Jixiang; Xu Jiaming; Guo Xiuhong (Carbonates and Evaporites, 2002)